Concerns underlying treatment preferences of advanced cancer patients with children. Issue 10 (26th May 2016) - Check, Devon K.; Park, Eliza M.; Reeder‐Hayes, Katherine E.; Mayer, Deborah K.; Deal, Allison M.; Yopp, Justin M.; Rosenstein, Donald L.; Hanson, Laura C.
Abstract: Background: Decision‐making about advanced cancer treatment is complex and may be influenced by patients' family context, including the presence of children. We explored how parental values and concerns motivate patients' preferences about aggressiveness of advanced cancer treatment as well as preferences for palliative care and hospice services. Methods: We conducted semi‐structured interviews with 42 patients with advanced cancer who had at least one child under 18 years. We created and applied thematic codes. Descriptive analyses were used to report the number of participants who mentioned each code. Results: The majority of participants (29/42) reported that having children influenced their preferences for advanced cancer care. For most parents, extending life to maximize the time they had left to parent their children was important in guiding treatment preferences. Others prioritized preserving their physical condition and parental functioning and remaining physically close to their children. Many parents discussed life extension and parental functioning preservation as competing priorities. Most of the sample expressed interest in palliative care services and hospice, but responses by several participants reflected concerns about dying at home and lack of clarity about the role of early palliative care. Conclusions: Parents in our sample expressed that maximizing time with their children and preserving parental functioning were important concerns underlying their preferences for advanced cancer care. Future research should assess the palliative and end‐of‐life care needs and preferences of parents with advanced cancer, which may differ from those of non‐parents. Copyright © 2016 John Wiley & Sons, Ltd.